2006
DOI: 10.1111/j.1601-1546.2008.00231.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of antibiotics in preventing healing complications after traumatic dental injuries: a literature review

Abstract: Traumatic dental injuries result in tissue damage and risk of infection. Experimental studies have shown various avenues for bacterial invasion following trauma: enamel infractions, dentinal tubules, exposed pulps, damaged periodontal ligament (PDL) and exposed alveolar bone. Hematogenous seeding of bacteria (anachoresis) may also occur during pulpal revascularization after trauma. The implication of these routes of entry differs according to the type of traumatic dental injury. It is known that bacterial colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 68 publications
0
28
0
4
Order By: Relevance
“…The revascularization process may be arrested at any level in the root canal if bacteria gain access to the ischemic part of the pulp. This scenario is discussed elsewhere (4).…”
Section: Pulpal Healing and Pulpal Necrosismentioning
confidence: 94%
See 1 more Smart Citation
“…The revascularization process may be arrested at any level in the root canal if bacteria gain access to the ischemic part of the pulp. This scenario is discussed elsewhere (4).…”
Section: Pulpal Healing and Pulpal Necrosismentioning
confidence: 94%
“…Other factors related to the risk of root resorption appear to be the presence of bacteria in the PDL (33), in the dentinal tubules or in the pulp, and the quality of endodontic treatment provided (34). These factors are discussed elsewhere (4). A relationship between the risk of root resorption complications and the tooth's stage of root development and the patient's age has been shown to exist as increasing age and root maturation adversely affect the risk of root resorption (1).…”
Section: Pdl Healing and Root Resorptionmentioning
confidence: 99%
“…Antibiotics (67)(68)(69)(70)(71)(72)(73)(74)(75)(76) The value of systemic administration of antibiotics in human after replantation is still questionable as clinical studies have not demonstrated its value. Experimental studies have, however, usually shown positive effects upon both periodontal and pulpal healing especially when administered topically.…”
Section: Follow-upmentioning
confidence: 99%
“…The results must, however, be evaluated with a certain amount of reservation as the risk of interference by confounding factors can never be eliminated with certainty. This type of analysis has so far offered useful information about the effect of various treatment procedures such as repositioning, type and length of splinting times (9, 10) and the use of antibiotics (11).…”
Section: Are Human Clinical Non‐randomised Studies a Valid Approach Tmentioning
confidence: 99%